Band limited chirp stimulation in vestibular evoked myogenic potentials - Walther, Leif Erik; Cebulla, Mario (European archives of oto-rhino-laryngology and head & neck, 2016)
Air conducted vestibular evoked myogenic potentials (VEMP) can be elicited by various low frequency and intense sound stimuli, mainly clicks or short tone bursts (STB). Chirp stimuli are increasingly used in diagnostic audiological evaluations as an effective means to obtain acoustically evoked responses in narrowed or extended frequency ranges. We hypothesized in this study that band limited chirp stimulation, which covers the main sensitivity range of sound sensitive otolithic afferents (around 500 Hz), might be useful for application in cervical and ocular VEMP to air conduction. For this purpose we designed a chirp stimulus ranging 250-1000 Hz (up chirp). The chirp stimulus was delivered with a stimulus intensity of 100 dB nHL in normal subjects (n = 10) and patients with otolith involvement (vestibular neuritis) (n = 6). Amplitudes of the designed chirp (“CW-VEMP-chirp, 250-1000 Hz”) were compared with amplitudes of VEMPs evoked by click stimuli (0.1 ms) and a short tone burst (STB, 1-2-1, 8 ms, 500 Hz). CVEMPs and oVEMPs were detectable in 9 of 10 normal individuals. Statistical evaluation in healthy patients revealed significantly larger cVEMP and oVEMP amplitudes for CW-VEMP-chirp (250-1000 Hz) stimuli. CVEMP amplitudes evoked by CW-VEMP-chirp (250-1000 Hz) showed a high stability in comparison with click and STB stimulation. CW-VEMP-chirp (250-1000 Hz) showed abnormal cVEMP and oVEMP amplitudes in patients with vestibular neuritis, with the same properties as click and STB stimulated VEMPs. We conclude that the designed CW-VEMP-chirp (250-1000 Hz) is an effective stimulus which can be further used in VEMP diagnostic. Since a chirp stimulus can be easily varied in its properties, in particular with regard to frequency, this might be a promising tool for further investigations.
Gesehen am 24.07.2019